2017
DOI: 10.4244/eij-d-17-00198
|View full text |Cite
|
Sign up to set email alerts
|

Which is the best antiaggregant or anticoagulant therapy after TAVI? A propensity-matched analysis from the ITER registry. The management of DAPT after TAVI

Abstract: After TAVI with a balloon-expandable prosthesis, aspirin alone does not increase the risk of prosthetic valve dysfunction, and reduces the risk of periprocedural complications and of 30-day all-cause death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 30 publications
1
53
0
Order By: Relevance
“…First, this study was limited by its retrospective single center design with corresponding limitations. Second, because of the retrospective design it was not possible to investigate other aspects of sarcopenia or frailty including muscle strength (e.g., handgrip strength) and muscle performance (e.g., gait speed) or factors influencing outcome such as antiaggregant/anticoagulant therapy …”
Section: Discussionmentioning
confidence: 99%
“…First, this study was limited by its retrospective single center design with corresponding limitations. Second, because of the retrospective design it was not possible to investigate other aspects of sarcopenia or frailty including muscle strength (e.g., handgrip strength) and muscle performance (e.g., gait speed) or factors influencing outcome such as antiaggregant/anticoagulant therapy …”
Section: Discussionmentioning
confidence: 99%
“…Sterling et al[29] revealed a trend towards an increased incidence of major/life-threatening bleeding when comparing DAPT to SAPT, with similar rates of stoke and death. One study also discovered that after TAVI with a balloon-expandable prosthesis, SAPT significantly reduced the rates of major vascular complications and major bleeding without having an impact on valve function[30]. Other studies also revealed similar outcomes[31-33].…”
Section: Discussionmentioning
confidence: 58%
“…The filter group was associated with a significant reduction of new cerebral lesions in the protected territories (4 vs. 10, p < 0.001) and in the entire brain (8 vs. 16, p = 0.002). Volume of these lesions was also lower in the filter group (466 vs. 800 mm 3 ; p = 0.02), with a total of 5 minor strokes in each treatment arm ( 54 58 , 68 70 ).…”
Section: Embolic Protection Devicesmentioning
confidence: 91%
“…Triple therapy (warfarin+DAPT, 4.5%) or left atrial appendage closure (0.5%) was marginally used as the standard care in patients with AF undergoing TAVI. Two observational studies showed no differences in terms of stroke, but lower bleeding rates in patients treated with warfarin alone compared to a combination of warfarin with one antiplatelet drug, especially with ASA ( 70 , 71 ). Another interesting alternative in patients with AF is to mechanically close the left atrial appendage in order to reduce bleeding events without jeopardizing stroke protection ( 72 ).…”
Section: Antithrombotic Therapymentioning
confidence: 98%